Thermohydrodynamic Characteristics of Worn Journal Bearing Lubricated With Oil Containing Nanoparticles Additive - Abass, Basim A.; Mohammed, Nadhim F. (Al-Nahrain Journal for Engineering Sciences, 2017)
In the present work the worn journal bearing is simulated to discuss the effect of adding TiO2 nanoparticles to the base oil on its thermal performance. An extensive numerical investigation is carried out to study the effect of different parameters affecting thermal performance of worn journal bearing such as the eccentricity ratio (?), the wear depth parameter (?), and the nanoparticle concentration (?). The computational approach is provided by using finite difference method for solving the governing equations, namely, the modified Reynolds equation, energy and heat conduction equations with suitable equation to include the variation of the oil film thickness due to the bearing wear in order to estimate the benefits of using nanolubricant in worn journal bearings. Oil viscosity dependence on nanoparticle concentrations is considered by using Krieger Dougherty model. The mathematical model as well as the computer program prepared to solve the governing equations were validated by comparing the oil film pressure distribution obtained in the present work for a worn journal bearing with that obtained numerically by Hashimoto et.al [2](1986) with 3% maximum deviation between the results. The maximum oil film pressure obtained in this work was compared with that obtained experimentally by Roy [12] (2009) for intact journal bearing with 3% as a maximum error between the results. The results obtained show that the nanoparticles addition by 0.5% and 1% to the base oil increases the load carrying capacity of the worn journal bearing by 20% and 40% respectively while decreases the oil side leakage by 5% and 10% and friction coefficient by 2.75% and 5.7% as compared to that lubricated with pure oil. This is happen with the expense of power losses. Calculations also shows that adding a higher percentage of nanoparticles (2%) has a harmful effect on the performance of a worn journal bearing since the power losses is highly increased.